Evaluation results of the tribological properties of aviation oils for aircraft engines - M. V. Seleznev; K. I. Gryadunov; K. E. Balyshin (Научный вестник МГТУ ГА)
The development of modern heat-stressed aircraft engines is a complex process based on the advanced achievements of various branches of science and technology, including chemmotology. Each new generation of aircraft engines imposes stricter requirements on the quality of the aviation oils used to ensure the reliable operation, including engine oil systems, rotor bearings and other components. One of the important factors in reducing friction and wear-out of modern gas turbine engines is the use of high-quality oils with a high level of anti-wear and anti-friction properties which allow engines to operate under various relubrication intervals. In the domestic regulatory and technical documentation, the anti-wear properties of aviation oils are evaluated using a four-ball friction machine according to GOST 9490, and the anti-friction properties are not taken into account. The specified friction machine has a variety of disadvantages. In this regard, the authors evaluated the anti-wear and anti-friction properties of domestic aviation oils using a versatile vibro-tribometer which allows for the operational properties of oils to be researched under the modes that are the most characteristic for the actual operation of aircraft engines compared with parameters of oil tests by a four-ball friction machine. Unlike the four-ball friction machine, the vibro-tribometer design implements a contact - interaction scheme in a “ball-plate plane” friction pair. At the same time, a thermal chamber is installed on this application that provides constant heating of the friction pair and the tested lubricating oils to the required temperature (from 0 to 150 ℃). It has been found that IPM-10 aviation oil possesses the best anti-wear and anti-friction properties, and with an increase in the tested oil temperature, a proportional increase in wear-out in the “ball-plate plane” friction pair occurs.